2010
DOI: 10.1097/brs.0b013e3181ecf6e4
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Use of Bone Morphogenetic Proteins in the United States Using Administrative Data

Abstract: At least 85% of principal procedures using BMP were for off-label applications. With uncertainty regarding the risks of using BMP in certain off-label applications, further research will be needed to better define the appropriate indications. Our study also demonstrates that disparities in the differential rates of BMP use exist in the spine fusion population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
165
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(168 citation statements)
references
References 33 publications
2
165
0
1
Order By: Relevance
“…We chose to use BMP-2 in this study based on the fact that BMP-2 has received FDA approval for bone regeneration (Ong et al 2010) and has been shown to promote dentin formation (Wang et al 2016). The fact that we found no calcified dental tissue formation in any BMP-2-loaded dTB implants emphasizes the importance of added cells for tooth regeneration in this model.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to use BMP-2 in this study based on the fact that BMP-2 has received FDA approval for bone regeneration (Ong et al 2010) and has been shown to promote dentin formation (Wang et al 2016). The fact that we found no calcified dental tissue formation in any BMP-2-loaded dTB implants emphasizes the importance of added cells for tooth regeneration in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Friedlaender et al (2001) demonstrated safe application of BMP-7 in vivo with non-union healing comparable to autograft controls. Together, these studies pioneered BMP-7 use in vivo and led to FDA approval for use in long bone non-unions in 2001 and posterolateral lumbar fusions in 2004 (Ong et al, 2010). Regarding lumbar fusion surgery, BMP-7 was delivered at 3.5 mg per vertebral side (7 mg in total).…”
Section: Bmp-7/op-1mentioning
confidence: 99%
“…Despite its off-label use, 30.0% of BMP use is in primary TLIF/ PLIF procedures and 20.4% of BMP is used in primary posterolateral spinal fusions [20]. Hence, the use of BMP for lumbar spinal fusions can be considered as an optional "standard of care" before the FDA has granted approval [20].…”
Section: Discussionmentioning
confidence: 99%